Hubungan Durasi dan Postur Duduk terhadap Terjadinya Nyeri Leher Pada Mahasiswa Fakultas Kedokteran Universitas Udayana - Lianto, Agatha Nadya; Muliani, .; Gede Wardana, I Nyoman; Yuliana, . (E-Jurnal Medika Udayana; Vol 10 No 7 (2021): Vol 10 No 07(2021): E-Jurnal Medika UdayanaDO - 10.24843/MU.2021.V10.i7.P05, 2021)
Neck pain is felt in the posterior cervical region. Neck pain is placed fourth on the global burden of musculoskeletal at the World Health Organization and impacts a person’s productivity. The cause of neck pain itself cannot be clearly identified, but several risk factors are associated with neck pain. For example, age, occupation, sitting posture, duration of sitting, stress, body mass index, smoking history and gender. This study aims to determine the relationship between duration and sitting posture on the occurrence of neck pain in students of the Faculty of Medicine, Udayana University. This study is a cross-sectional analytic study that uses the NDI (Neck Disability Index) questionnaire. Neck pain intensity poin used to assess the occurrence of neck pain. This study had 206 research subjects. The data were analyzed using IBM SPSS statistic version 20. The chi-square test results showed that a significance value of 0.338 for the relation between sitting duration and the occurrence of neck pain, and a value of 0.949 for the relation between sitting posture and the occurrence of neck pain. From the analysis, it was found that there were no correlation between sitting duration and sitting posture on the occurrence of neck pain in students of the Faculty of Medicine, University of Udayana. It is necessary to do further research on other factors that can cause neck pain in students. Keywords : neck pain, sitting duration, sitting posture, Neck Disability Index